2015
DOI: 10.1016/j.freeradbiomed.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus onset in lupus-prone B6.MRL/lpr mice Is influenced by weight gain and Is preceded by an increase in neutrophil oxidative burst activity

Abstract: In this study, we assessed whether weight gain influenced the systemic lupus erythematosus (SLE) onset and/or outcome, and examined the role that reactive oxygen species (ROS) production by neutrophils played in the SLE onset and/or outcome. Female control (C57BL/6) and lupus-prone B6.MRL/lpr mice (CM and LPM, respectively) at 4 weeks old were fed standard diet or standard diet plus cafeteria diet during 12 weeks. SLE diagnosis relied on the presence of both antinuclear antibodies (ANA) and renal abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…It suggested that the 8-week-old lupus-prone mice were at the pre-lupus state, and most of 14-week-old mice exhibited characteristic laboratorial and clinical symptoms of SLE. The result was consistent with the previous report [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It suggested that the 8-week-old lupus-prone mice were at the pre-lupus state, and most of 14-week-old mice exhibited characteristic laboratorial and clinical symptoms of SLE. The result was consistent with the previous report [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…The MRL/lpr mouse is a widely accepted spontaneous murine model of SLE, featuring numerous autoantibodies, proteinuria, and representative manifestations of SLE (e.g., splenomegaly, lymphadenopathy, and IC glomerulonephritis) [ 20 , 21 ]. Moreover, it has been demonstrated that most mice display lupus symptoms at 12 weeks of age [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten mice per group were used to carry out behavioral detection. The majority of the 16-week-old MRL/lpr mice exhibited characteristic cognitive dysfunctions [ 46 ]. Morris water maze (MWM) test was conducted to assess hippocampus-dependent spatial learning and memory functions in rodents [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the 16-week-old MRL/lpr mice exhibited characteristic cognitive dysfunctions [45], as assessed by behavioral assays. Morris water maze (MWM) test was conducted to assess hippocampusdependent spatial learning and memory functions in rodents [46,47].…”
Section: Behavioral Assaysmentioning
confidence: 99%